Leaching of flame-retardants from polystyrene debris: Bioaccumulation and potential effects on coral. (February 2020) - Aminot, Yann; Lanctôt, Chantal; Bednarz, Vanessa; Robson, William J.; Taylor, Angus; Ferrier-Pagès, Christine; Metian, Marc; Tolosa, Imma
Abstract: Marine plastic debris can act as a reservoir of chemical additives that can pose a potential threat to sensitive ecosystems such as coral reefs. A survey of foam macrodebris collected on beaches indeed revealed high concentrations of hexabromocyclododecanes (ΣHBCDD) in polystyrene (PS) samples (up to 1940 μg g −1 ). Results also showed that PS fragments can still leach over 150 ng g −1 d −1 of ΣHBCDD (primarily as the α-isomer) for relatively long durations, and that these additives are readily bioaccumulated and well-retained by corals. Despite significant HBCDD bioaccumulation in coral tissue, short-term exposure to HBCDD or PS leachate had no considerable effect on coral photosynthetic activity, symbiont concentration and chlorophyll content. Exposure to the PS leachate did however cause consistent polyp retraction in nubbins over the 5-day exposure. This response was not observed in animals exposed to HBCDD alone, suggesting that another constituent of the leachate stressed corals. Graphical abstract: Unlabelled Image Highlights: Most beached foam macrodebris had elevated concentrations of HBCDD. HBCDD containing polystyrene can release additives over relatively long durations. Corals can bioaccumulate these brominated flame retardants. Polyp retraction was the only short-term observed physiological effect of leachate.